A systematic review on concentration of residential indoor air metals and health risk assessment - Ali Momen; Arezo Rezaie; Roohollah Rostami (Journal of Air Pollution and Health)
This review evaluates metal concentrations in indoor air within residential buildings, focusing on original research published in English from 2010 to 2022. We conducted a comprehensive literature search across Google Scholar, ScienceDirect, and SpringerLink, identifying 34 relevant studies measuring metal concentrations in various residential environments. Data extraction revealed significant regional variations, with urban homes exhibiting higher metal concentrations compared to rural and industrial areas. Chromium (Cr) levels in urban regions reached 116.00±170.00 mg/kg, compared to 63.40±34.80 mg/kg in rural areas and 30.90±16.90 mg/kg in industrial regions. Nickel (Ni) concentrations were also higher in urban homes at 86.10±126.00 mg/kg, versus 27.60±9.08 mg/kg in rural and 20.40±7.65 mg/kg in industrial settings. The living room showed the highest metal concentrations, with lead (Pb) at 170.00±NA mg/kg and nickel (Ni) at 174.00±144.00 mg/kg, significantly higher than in bedrooms and kitchens (p<0.05). Seasonal variations indicated elevated warm season metal concentrations, with iron (Fe) measured at 11,200 ± 9830 mg/kg. Health risk assessments highlighted a total cancer risk (CR) of 1.59 × 10⁻³ in industrial areas, exceeding acceptable limits (10⁻5 to 10⁻⁶). The ingestion pathway was the primary route for both cancer and non-cancer risks, with copper (Cu) posing the highest potential cancer risk across all regions. These findings emphasize the need for monitoring and regulation of indoor metal concentrations, particularly in industrial areas.